Evidence Based Nursing Penatalaksanaan Stroke melalui Penggunaan Mobile Health Terhadap Pengendalian Paska Stroke - Frida Voliana; Yunita Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of using the mHealth application in stroke patients in post-stroke control. The method used is an article search using electronic databases such as the Cochrane Library, Ebsco, Pubmed, Sage Journals, and Science Direct. The study results show that an indicator of effectiveness is that mHealth can prevent secondary strokes in stroke patients and prevent disability in post-stroke patients. Were 199 articles found, and then nine were selected for criticism/analysis. Among the nine articles found in this study, the patient characteristics were almost the same, and it was found that mHealth was effective in post-stroke control, namely secondary stroke prevention and post-stroke disability management. In conclusion, mHealth is the best tool for post-stroke control compared to traditional health counseling, community essential health services, conventional daily programs, or classic pamphlets. Keywords: Cellular Health, Disability Management, Secondary Prevention, Stroke